How the Justice Power Post Constitution Amendment? A Review Book "Politik Hukum Kekuasaan Kehakiman Pasca Amandemen Undang-Undang Dasar 1945", Ma'shum Ahmad, Total Media Yogyakarta, 2017, 193 pages, ISBN: 979-1519-25-0 - Ataupah, Andrew Mario Ernesto (JILS (Journal of Indonesian Legal Studies), 2021)
This book examines and describes the relationship between the rule of law, legal politics, and the legal political configuration of judicial power, the functions and authorities of the Supreme Court, the functions and authorities of the Constitutional Court, the functions and authorities of the Judicial Commission. old, new and reform orders.